Experiences of occupational therapists within an ACT-based interdisciplinary pain management program - Maria Haage; Carina Tjörnstrand (Scandinavian Journal of Occupational Therapy)
Background Acceptance and Commitment Therapy (ACT)-based interdisciplinary pain rehabilitation programs have shown effective results. While occupational therapy within these programs has made a unique contribution to pain management because of its focus on occupation and use of group activities, little is known about occupational therapists’ own experiences of it.Aim The aim of this study was to describe the occupational therapists’ experiences of working in a manual-based interdisciplinary pain management program grounded in ACT.Material and methods Six occupational therapists at a pain rehabilitation clinic were interviewed. Data were analysed using Braun and Clark’s thematic analysis.Results The occupational therapists experienced that ACT and occupational therapy complement each other and that ACT facilitated comprehension of occupational therapy interventions. With ACT, the team gained a common language, which made teamwork and patient comprehension more efficient. A behavioural analysis (SORC) served as a link between occupational therapy and ACT.Conclusions Manual-based occupational therapy activity group interventions with elements of ACT were felt to enhance the patient’s understanding of their rehabilitation and supported teamwork.Significance This study provides further support for use of ACT in occupational therapy within interdisciplinary pain management programs. Occupational therapistsˈ use of SORC is an area of development.